Developing Entrepreneurial Attitude through Soap Making Chemistry Practicum in High School: Need Analysis - Titin Nurhayatin; Bambang Susilo; Suyanta (Postgraduate, University of Mataram, 2025)
This study aims to explore how chemistry practicum activities can contribute to the development of students' entrepreneurial attitudes at SMA Negeri 3 Ketapang. This study was conducted at SMA Negeri 3 Ketapang, West Kalimantan, with respondents consisting of 352 students in grades X and XI and 20 chemistry teachers. Data were collected through a 30-item questionnaire based on a five-point Likert scale, which measures six aspects of entrepreneurial attitude, namely self-confidence, task and result orientation, risk-taking, leadership, future orientation, and creativity. The results showed that students recorded the highest score on the risk-taking aspect (74.63%) and the lowest on creativity (56.99%). The teachers showed a similar pattern, with the highest score for the risk-taking aspect (69.00%) and the lowest for the creativity aspect (56.00%). There was little difference in scores between students and teachers, indicating that both groups value entrepreneurial attitudes in education. This study concludes that chemistry practicum enhances students' entrepreneurial attitudes, especially risk-taking and leadership. However, creativity needs more attention to be effectively integrated into the learning process.